Decoupling economic growth from water consumption in the Yangtze River Economic Belt, China - Yang Kong (Elsevier, 2021)
Decoupling economic growth (EG) from water consumption (WC) is crucial to regional sustainable development. Therefore, it is necessary to analyze the spatial and temporal decoupling of WC and EG, and then to identify the feasible paths for achieving the desired level of decoupling. Firstly, this paper measures the WC of the provincial areas in the Yangtze River Economic Belt (YREB) from 2004 to 2017 by using the water footprint (WF) method; Secondly, the decoupling analysis of WF and EG is carried out based on the Tapio decoupling model, furthermore, the spatial autocorrelations of decoupling results are examined by the Moran’s I index with three different spatial weight matrices; Finally, the paths of achieving strong decoupling (SD) of WC and EG are explored by using the static fixed effect regression model. Three main conclusions can be drawn: (1) The WFs of most provincial areas in the YREB show an overall increasing trend and there are huge disparities among the provinces in terms of their WFs; (2) The WF and EG in the YREB are decoupled either strongly or weakly. More SD has been achieved since 2015 in general. No spatial autocorrelations are observed; (3) Reducing the WF as the economy grows is a necessary condition for achieving SD. Moreover, developing water-saving technologies is a key path of achieving SD since it has huge positive impact on WF reduction. In a nutshell, this study provides a novel framework and results that can be used as an evaluation index and policy insights for decoupling EG from WC.